Executioner Caspase-3 and 7 Deficiency Reduces Myocyte Number in the Developing Mouse Heart - Cardona, Maria (Public Library of Science, 2015)
Executioner caspase-3 and -7 are proteases promoting cell death but non-apoptotic roles are being discovered. The heart expresses caspases only during development, suggesting they contribute to the organ maturation process. Therefore, we aimed at identifying novel functions of caspases in heart development. We induced simultaneous deletion of executioner caspase-3 and -7 in the mouse myocardium and studied its effects. Caspase knockout hearts are hypoplastic at birth, reaching normal weight progressively through myocyte hypertrophy. To identify the molecular pathways involved in these effects, we used microarray-based transcriptomics and multiplexed quantitative proteomics to compare wild type and executioner caspase-deficient myocardium at different developmental stages. Transcriptomics showed reduced expression of genes promoting DNA replication and cell cycle progression in the neonatal caspase-deficient heart suggesting reduced myocyte proliferation, and expression of non-cardiac isoforms of structural proteins in the adult null myocardium. Proteomics showed reduced abundance of proteins involved in oxidative phosphorylation accompanied by increased abundance of glycolytic enzymes underscoring retarded metabolic maturation of the caspase-null myocardium. Correlation between mRNA expression and protein abundance of relevant genes was confirmed, but transcriptomics and proteomics indentified complementary molecular pathways influenced by caspases in the developing heart. Forced expression of wild type or proteolytically inactive caspases in cultured cardiomyocytes induced expression of genes promoting cell division. The results reveal that executioner caspases can modulate heart’s cellularity and maturation during development, contributing novel information about caspase biology and heart development.